The evaluation of the sustainability of the communal property association farming project of the Shigalo wa Muhunguti Community, in Vhembe District of the Limpopo Province - Nkuna, Magezi Johannes (My University, 2013)
This research project unfolds within the Shigalo wa Muhunguti Communal Property Association farms at Tshitungulu, (Levubu) area, under Makhado Municipality in Vhembe District of the Limpopo Province, with the purposes to evaluating the sustainability of that Land Restituted farming project. This is a case study research project where both the qualitative and the quantitative research strategies were used. Data was collected through structured and semi-structured interviews. The analysis reveals that while the Land Reform programme has managed to restore land rights to the legitimate owners, the sustainability and continued productivity of such properties in the hands of the new owners remains a cause for major concern. The findings reveal among other things the low literacy level, lack of farming skills, low interest and passion for farming, and high level of dissatisfaction of employees. Poor marketing of produce is also a cause for great concern. Recommendations to address the above findings suggest that the Department of Agriculture should implement massive training programmes on beneficiaries, young farmers should be exposed to modern production system, regular meetings with employees could reduce their dissatisfaction, while the executive members could undergo vigorous training to get marketing skills to negotiate the sale of their produce.
Thesis (M.Dev.) --University of Limpopo, 2013
Keywords: Farming projects; Land reforms; 630.6825; Farm management; Industrial project management